ANALISIS SOCIAL RESPONSIBILITY DISCLOSURE PADA PERBANKAN SYARIAH BERDASARKAN GLOBAL INITIATIVE REPORTING INDEX DAN ISLAMIC SOCIAL REPORTING INDEX - kharisma, nailul (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The purpose of this researchÂ  is to compare the social responsibility disclosure of Islamic banks listed in Bank Indonesia on the period of 2014. Responsibility disclosure is measured by the Global Reporting Initiative Index and Islamic Social Reporting Index Index. This type of research used in this study is the calculation of the value of the scoring of each index, and hypothesis testing. By using content analysis and test independent t-test, 11 population fulfilling the criteria of Islamic banks in social responsibility disclosure. The data type is secondary data obtained through the annual reports from the official websites of each Islamic bank.The results of this research indicate that there are significant differences standard between of the social responsibility disclosure of Islamic banks using the Global Reporting Initiative Index and social responsibility disclosures of Islamic banks using Islamic Social Reporting Index. Social responsibility disclosure based Islamic Social Reporting Index is known to produce a higher scoring value for the banking company. Thus type disclosure is considered better to represent the disclosure of the responsibility of Islamic banks in Indonesia. Although the disclosure is based on Global Reporting Initiative standards have a more specific disclosure on the themes disclosed, but type disclosure is considered to be representative disclosure of social responsibility of Islamic banking. Thus, it can be concluded that there is a significant differences between the social responsibility disclosure using a standard Global Reporting Initiative Index and social responsibility disclosure using a standards Islamic Social Reporting Index.Keywords: social responsibility, disclosure reports, the Global Reporting Initiative Index, and the Islamic Social Reporting Index